Categorias funcionais da avifauna em resposta à estrutura da vegetação de áreas ripárias em restauração - Batisteli, Augusto Florisvaldo (2015)
Through the last decades, forest remnants were widely converted in crops and pastures, but the reintroduction of native trees offers the perspective of forests ecosystems restoration. This study aimed to investigate the recolonization by birds in riparian restored and reference sites, evaluating the effects of vegetation structure on avifaunal functional categories. We estimated vegetation structure by grass cover, tree density, total basal area, crown depth, height and diameter at breast height of each individual. We classified bird species by diet, foraging strata, nest height, dependence of cavities for nesting and forest dependence. To assess which characteristics were influenced by vegetation structure, we conducted canonical correspondence analysis, using as independent variables the three first axis of principal component analysis of vegetation variables, respectively related to canopy height, crown depth and stratification. We recorded 53 bird species in 326 registers. The avifauna of reference sites were richest and more diverse in all bird taxonomic descriptors. Canopy height influenced avifauna in relation to diet, foraging strata and forest dependence, and combinations of these functional traits also were affected by canopy height and crown depth. Species related to most open sites were granivorous or generalists with low forest dependence. Understory bird species occurred mainly in intermediate stages of vegetation growth, presenting middle forest dependence and more restrict diet. Insetivorous birds with high forest dependence characterized reference sites, with tallest vegetation. Our results emphasized the importance of considering functional traits of bird species on planning and evaluating recolonization of restored sites by birds. Considering the effects of riparian vegetation structure on bird assemblages, we suggest that reintroduction of plant life-forms other than trees for restoration purposes can accelerate both bird taxonomic and functional diversity across recolonization process.